Vitamin D Metabolism and Action in Human Marrow Stromal Cells: Effects of Chronic Kidney Disease - Zhou, Shuanhu (2012)
Human marrow stromal cells (hMSCs) are targets of 1! ,25-dihydroxyvitamin D [1! ,25(OH)(2)D(3)] action to promote their differentiation to osteoblasts, but they also participate in vitamin D metabolism by converting 25-dihydroxyvitamin D(3) [25(OH)D(3)] to 1! ,25(OH)(2)D(3) by 1α-hydroxylase (CYP27B1). Chronic kidney disease (CKD) is associated with impaired renal biosynthesis of 1! ,25(OH)(2)D, low bone mass, and increased fracture risk. We tested whether CKD influences hMSCs' responses to vitamin D(3) metabolites. The hMSCs were obtained from tissues discarded during arthroplasty for hip osteoarthrosis, including a subject who had been undergoing hemodialysis for 2+ years. There was a significant positive correlation between in vitro stimulation of osteoblastogenesis (alkaline phosphatase activity) by 1! ,25(OH)(2)D(3) and subjects' estimated glomerular filtration rate (eGFR, r=0.47, p=0.015, n=26, 56–83 years of age). Osteoblastogenesis was stimulated in hMSCs from both the hemodialysis and control subjects by 1! ,25(OH)(2)D(3) (10 ! M), 25(OH)D(3) (100 ! M), or D(3) (1000 ! M). Thus, vitamin D metabolism may play an autocrine/paracrine role in osteoblast differentiation of hMSCs. These findings suggest that in CKD patients 25(OH)D-sufficiency may play an important role in skeletal health; osteoblastic bone formation in CKD patients may not be optimal unless there is sufficient serum 25(OH)D substrate for the MSCs to synthesize and respond to local 1! ,25(OH)(2)D.